2019
DOI: 10.1111/phpp.12473
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to optical safety guidelines for laser‐assisted hair removal

Abstract: Background In recent years, there was a rise in ocular injuries secondary to cosmetic laser‐assisted hair removal. Purpose To assess the level of adherence to optical safety guidelines during laser‐assisted hair removal performed by nurses or physicians in private practice. Methods A cross‐sectional study was conducted at thirty‐one private laser‐assisted hair removal clinics. An electronic random number generator using a cluster random sampling technique was used to select the clinics. The Alexlazr™ (Candela … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The 2 most common areas of noncompliance were having reflective flooring or surfaces in the treatment rooms and lack of appropriate and prominent warning signs outside of treatment rooms. 15…”
Section: Resultsmentioning
confidence: 99%
“…The 2 most common areas of noncompliance were having reflective flooring or surfaces in the treatment rooms and lack of appropriate and prominent warning signs outside of treatment rooms. 15…”
Section: Resultsmentioning
confidence: 99%
“…In 62% of the cases, eye protection was not worn at the moment of laser application [2]. A literature review regarding the adherence to optical safety guidelines for laser hair depilation found that 72,3% of the cosmetic centers had a lack of nonreflective floors and 59,6% of the providers did not instruct patients not to look into the laser beam or its reflection even while wearing protection goggles [5].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted to evaluate the amount of adherence to optical safety criteria in centres performing laser-assisted epilation, it was determined that only 9.5% of the implementing facilities met the appropriate level of adherence. 7 Before beginning laser epilation, eye protection or glasses must be worn by the patient, the practitioner, and every observer in the area. Each device demands the use of proper eye protection or glasses based on its wavelength.…”
Section: Article In Pressmentioning
confidence: 99%
“…1 Patients should be informed of basic safety precautions such as avoiding staring directly into the laser beam, even when wearing safety glasses. 7 Patients should be informed of any potential dangers associated with laser epilation. Because the thin structure of the eyelid skin allows laser energy to penetrate deep ocular structures, periocular laser epilation applications involve significant dangers.…”
Section: Article In Pressmentioning
confidence: 99%